DEVELOPMENT OF A MULTIUSER-BASED LIBRARY INFORMATION SYSTEM IN THE LIBRARY AND ARCHIVES OFFICE, DEMAK DISTRICT - Mutiara Anggita Saputri; Budi Hartono (Lembaga Pengembangan Kinerja Dosen, 2021)
The purpose of this Multiuser-Based Library Information System Design at the Demak Regency Library and Archives Office is to help librarian in managing book data, member data, borrowing data, returning data and reports made by librarians who have been computerized but are still single users and are now computerized. and multiuser based. The system currently running at the Demak Regency Library and Archives Office, namely the database used sometimes still has errors when the officer inputs loan and return transactions, because the input data cannot be stored in the database. Library members find it difficult to see all the collections of books in the library because there is no adequate search for books. Reports submitted by officers are less efficient so that the head of the library is less clear in submitting his report. With the design of this multiuser-based library information system application, it can improve the quality and performance of this library. The methodology used in the Design of a Multiuser-Based Library Information System is the Research and Development Research and Development Method.